Antimicrobial activity of selected Malaysian medicinal plants / Jamal Houssaini - Houssaini, Jamal (Research Management Institute (RMI), 2012)
Antibiotic resistance in human pathogens due to increasing abuse of drugs has reached an alarming stage. The options in combating multiple drug resistance organisms are decreasing; hence there is a desperate need of new antimicrobial drugs. Several Malaysian medicinal plants have been used in traditional folk medicine for the treatment of various conditions. The purpose of this study is to investigate the anti-microbial activity of selected Malaysian medicinal plants in vitro and to detect the acute toxicity of the plants in experimental animals. The plants to be screened are Psidium guajava Linn (leaf), Illicium verum Hk.f. (fruit), and Swietenia macrophylla (seed). The medicinal plant extracts will be tested by in vitro antibacterial test against six bacterial species, both Gram positive and Gram negative organisms. Disc-diffusion assay (Bauer et al., 1966) will be employed for assessing antimicrobial activity. The plants will be subjected to acute toxicity study, using experimental laboratory animals. With the help of the natural product obtained from these plants we hope to fight the emerging multiple drug resistance and increasing cost of drugs. There are more than 35 000 plant species being used in the world that are useful for medicinal purposes. In peninsular Malaysia, 1200 species of higher plants and 2000 species in Sabah and Sarawak were reported to show medicinal properties and were also used for traditional health care (Jantan, I., 1998 ; Koshy Philip et al, 2009). In this study, we chose the plants that we used based on its traditional usage, the availability in Malaysia, and also based on previous researches information of its usage that has been proven together with their active chemical constituents that may help us to achieve our objectives.